WHAT WOOD IS THAT? : A Manual Of Wood Identification with 40 actual wood samples and 79 illustrations in text - Edlin, Herbert L. (Herbert Leeson) 1913-1976 640330 (London : Stobart Davies, 1977)
A unique book containing a fold-out wallet with 40 actual veneer samples. Each wood is described in terms of 14 key characteristics to teach the method of identifying these and other woods.